The Role of NMDA Receptors in Extinction of Cocaine Self-Administration - (:unkn) unknown (My University, 2013)
Relapse is highly prevalent among recovering addicts, and can be triggered by associations made between the rewarding effects of the drug and cues, such as drug paraphernalia or contexts. Inhibiting these associations, through new extinction learning, could help reduce relapse rates. Extinction is formed in phases, like other types of memory. The memory first is acquired in short-term memory, then is consolidated into long-term storage from which it can be retrieved at a later time (Quirk & Mueller, 2008). NMDA receptors are necessary for extinction in other paradigms (Santini, Muller, & Quirk, 2001), and we previously found that blocking NMDA receptors before four 45-minute extinction sessions disrupts retention when tested during a subsequent full extinction session. However, it is unclear which learning phase was disrupted. To determine how NMDA receptors affect extinction of cocaine self-administration, rats were trained to lever press for i.v. infusions of cocaine. Following training, rats underwent four 45-minute extinction sessions and received post-extinction session systemic injections of either the NMDA receptor antagonist CPP or the NMDA receptor coagonist D-serine. I hypothesized that CPP would disrupt extinction learning, and D-serine would facilitate extinction learning. Post-extinction session injections of CPP did not disrupt the consolidation of extinction, but instead appears to facilitate extinction. Alternative explanations such as pharmacological side effects or disrupted reconsolidation could explain these results. Post-session injections of D-serine facilitated consolidation of extinction compared to controls. These studies indicate that NMDA receptors are necessary for acquisition and maybe consolidation of extinction, and potentiating NMDA receptors will facilitate extinction learning. Additionally, western blotting was conducted on ventral medial prefrontal cortex (vmPFC) and nucleus accumbens (NAc) tissue to determine glutamate receptor expression following extinction of cocaine self-administration, withdrawal from cocaine, or extinction of sucrose reinforcement. Results indicated a trend for increased NR2B-containing NMDA receptor expression in the vmPFC after extinction of sucrose reinforcement and increased expression of NR2A- and NR2B-containing NMDA receptors in the NAc following cocaine withdrawal compared to expression following extinction of sucrose reinforcement. Thus, these studies indicate that cocaine use and extinction learning can induce changes with NMDA receptors in the NAc and possibly vmPFC.
Keywords: Extinction; Learning; NMDA; Self-Administration